Paralysis Due to Hypokalemia and Hypocalcemia: A Case Report - Ivanna Sarahfebi; Anastasia Nadya; Anisya Lisna; Parbati Anjali; Theresia Monica Rahardjo; Valentine Natasya Moenardi (Medical Clinical Update, 2022)
Background Hypokalemia is the most frequent electrolyte disorder encountered in clinical practice. It caused by inadequate potassium intake or excessive renal or gastrointestinal potassium loss. Hypokalemia may associate with muscle weakness. Hypocalcemia can result from disorders of vitamin D metabolism and action, hypoparathyroidism, resistance to parathyroid hormone (PTH), or other conditions such as nutritional deficiency. Numbness and tingling sensation may occur on hypocalcemia. Case presentation A 36-year-old woman came with complaints of weakness of upper and lower limbs three days before admission. At first, the weakness felt suddenly on the left arm and left foot after waking up in the morning, making her not being able to walk. Patient felt tingling sensation on her face, upper limbs, and lower limbs. Her hands felt stiff as well as her mouth. Patient had a decreasing serum level (3 mEq/l) and decreasing total calcium level (4,8 mg/dL). Conclusion In young adult patients with limbs weakness, it is necessary to consider electrolyte imbalance, such as hypokalemia and hypocalcemia. Hypokalemia can be caused by decreased potassium intake, excessive vomiting, drug consumption, kidney disease, and endocrine disease. To diagnose hypokalemia, it is necessary to carry out further examinations such as basic biochemical laboratories (magnesium, calcium, phosphorus), blood gas analysis, TSHs, urine analysis (urine calcium, potassium excretion in 24-hour urine collection), drug screening.